Encounters with a radical Erasmus : Erasmus' work as a source of radical thought in early modern Europe - Bietenholz, Peter G. (Erasmus studies., 2009)
An engaging look at Erasmus' theological, philosophical and socio-political influence, Encounters with a Radical Erasmus will prove useful to scholars of humanism, theology, the Reformation and Renaissance.